The Conditions and Development Guidelines for Financial Management Based on Good Governance Principles in Educational Institutions Under the Secondary Educational Service Area Office Phra Nakhon Si Ayutthaya. - KITTHANASATIEN, METHAPAT (Journal of Innovative Business Management Research, 2025)
This research aims to study the current state of financial management based on good governance principles in schools under the Secondary Educational Service Area Office of Phra Nakhon Si Ayutthaya and to explore development guidelines for financial management according to these principles in the same schools. The research was conducted in 2 steps: Step 1) Study the financial management based on good governance principles in the mentioned schools. The sample group consisted of 87 school administrators, financial heads, and financial officers. The research tool used was a questionnaire, and data were analyzed using frequency, percentage, mean, and standard deviation statistics. And Step 2) development guidelines for financial management based on good governance principles in schools under the Secondary Educational Service Area Office of Phra Nakhon Si Ayutthaya. Five experts with knowledge and expertise in financial management provided data through interviews, which were analyzed using content analysis. The research findings revealed that 1) The study on the current state of financial management based on good governance principles in schools under the Secondary Educational Service Area Office of Phra Nakhon Si Ayutthaya found that overall, the average level was high. When considering each aspect, the aspect with the highest average was the management of treasury funds and deposits, which was at the highest level, followed by the disbursement of funds, which was at a high level. The aspects with the lowest averages were payment and cash custody, both of which were at high levels. And 2) The development guidelines for financial management based on good governance principles in schools under the Secondary Educational Service Area Office of Phra Nakhon Si Ayutthaya found that financial management in schools should adhere to good governance principles, covering the rule of law, morality, transparency, participation, accountability, and value for money. Additionally, the financial management system should be developed into a digital system to increase accuracy, reduce duplication of work, and facilitate practices, allowing for convenient tracking and auditing. The guidelines also suggested promoting participation from all sectors in budget planning and expenditure auditing to build trust and transparency in management. Regular annual training should be provided to teachers and related staff to enhance their knowledge and skills in financial matters, enabling them to understand new regulations and systems related to financial work and reducing operational errors. Furthermore, integrity and accountability should be promoted, and channels should be opened for reporting tips or complaints about corruption cases without revealing names, to enhance.